Dispute resolution by Courts and Dispute resolution in court. Partners or rivals? - Kristin Hero (Oñati Socio-Legal Series)
This session of the workshop was dedicated to alternative dispute resolutions (ADR), which consists of dispute resolution processes and techniques through which disagreeing parties come to an agreement without having to litigate. Despite historic resistance, over the years ADR has gained widespread acceptance among both the general public and the legal profession. In the discussion there was a specific emphasis on mediation and arbitration.